Effectiveness of Virtual Account Integrated Academic Information System for Increased Educational Efficiency and Transparency - Nur, Fauziah; Akbar, Muhammad Caesar; Sukarwoto, Sukarwoto; Ulfa, Sylvia (Al-Makki Publisher, 2024)
Academic information system (SIAKAD) plays an important role in the management of educational data in higher education institutions. This study aims to evaluate the effectiveness of an academic information system integrated with virtual accounts at Medan Aviation Polytechnic, in order to improve efficiency and transparency in financial management. This research uses R&D (Research & Development) method with waterfall software development model. Data was collected through observation, interviews, questionnaires, and documentation. Observations were conducted to understand the data processing process, while interviews and questionnaires were used to obtain input from the study program admin and academic admin. The results showed that the integrated academic information system has functioned well. Features such as KRS filling, transcript printing, and payment confirmation can be accessed by various users, including university admins, study program admins, lecturers, and students. Users reported increased efficiency in managing academic and financial data. The implementation of SIAKAD integrated with virtual accounts provides significant benefits in terms of transparency and reduction of human error in data processing. The system facilitates real-time access to information, which is essential for informed decision-making in education management. This study concludes that the implementation of SIAKAD integrated with virtual accounts is effective in improving the efficiency and transparency of academic and financial data management at Politeknik Penerbangan Medan. Recommendations for further development include enhancing system features to support diverse user needs.